Question

solve the initial value problem y''-2y'+5y=u(t-2) y(0)=0 y'(0)=0

solve the initial value problem y''-2y'+5y=u(t-2) y(0)=0 y'(0)=0

Homework Answers

Know the answer?
Your Answer:

Post as a guest

Your Name:

What's your source?

Earn Coins

Coins can be redeemed for fabulous gifts.

Not the answer you're looking for?
Ask your own homework help question
Similar Questions
Use Laplace transforms to solve the given initial value problem. y"-2y'+5y=1+t y(0)=0 y’(0)=4
Use Laplace transforms to solve the given initial value problem. y"-2y'+5y=1+t y(0)=0 y’(0)=4
Please solve the listed initial value problem: y'' + 3y' + 2y = 1 - u(t...
Please solve the listed initial value problem: y'' + 3y' + 2y = 1 - u(t - 10); y(0) = 0, y'(0) = 0
For the initial value problem • Solve the initial value problem. y' = 1/2−t+2y withy(0)=1
For the initial value problem • Solve the initial value problem. y' = 1/2−t+2y withy(0)=1
For 2y' = -tan(t)(y^2-1) find general solution (solve for y(t)) and solve initial value problem y(0)...
For 2y' = -tan(t)(y^2-1) find general solution (solve for y(t)) and solve initial value problem y(0) = -1/3
Solve the initial value problem below for the Cauchy-Euler equation t^2y"(t)+10ty'(t)+20y(t)=0, y(1)=0, y'(1)=2 y(t)=
Solve the initial value problem below for the Cauchy-Euler equation t^2y"(t)+10ty'(t)+20y(t)=0, y(1)=0, y'(1)=2 y(t)=
Solve the initial value problem y''−y'−2y=0, y(0) = α, y'(0) =2. Then find α so that...
Solve the initial value problem y''−y'−2y=0, y(0) = α, y'(0) =2. Then find α so that the solution approaches zero as t →∞
for the given initial value problem: (2-t)y' + 2y =(2-t)3(ln(t))    ; y(1) = -2 solve the...
for the given initial value problem: (2-t)y' + 2y =(2-t)3(ln(t))    ; y(1) = -2 solve the initial value problem
Consider the initial value problem 2y′′+11y′+5y=aδ(t−1), y(0)=y′(0)=0 , where δ denotes the impulse function. Suppose that...
Consider the initial value problem 2y′′+11y′+5y=aδ(t−1), y(0)=y′(0)=0 , where δ denotes the impulse function. Suppose that the solution of this initial value problem satisfies y(3)=(e^9−1)/e^10. Find the value of a.
Solve the initial value problem y = 3x^2 − 2y, y(0) = 4
Solve the initial value problem y = 3x^2 − 2y, y(0) = 4
Solve the initial value problem y' = 3x^2 − 2y, y(0) = 4
Solve the initial value problem y' = 3x^2 − 2y, y(0) = 4